Analytical Approach To Mechanical Damage Of Reefer Container On MV. Cap San Juan: Case Study And Optimization Recommendations - Andromeda, Farrel; Wibowo, Wahju; Nurhidayati, Indah (Nama Jurnal Akmi, 2024)
Ships used for shipping goods, especially on the MV. Cap San Juan there are things that must be considered, one of which is the reefer container which has strict maintenance and control to know that the reefer container can work optimally. In this case the reefer container has a risk of damage to its components so that the reefer container does not function as it should. Therefore, it is necessary to discuss as a form of effort in handling if damage occurs and unwanted obstacles occur. This study aims to determine the causes and effects of mechanical damage to reefer containers on ships and to find out how to overcome reefer containers that experience mechanical damage on the high seas based on field conditions. The research method used is a qualitative method using data collection techniques through observation, interviews and documentation regarding the handling of reefer containers when problems occur. Based on the results of observations made by the author regarding the various obstacles that occur in reefer containers during sea practice, there are two causes, namely component damage because it has passed the time limit for use and an electrical short circuit in one of its components which causes the reefer container to not be able to work optimally. This happened because there was no thorough checking and lack of maintenance.